Bombing civilians : a twentieth-century history / a twentieth-century history - Tanaka, Toshiyuki, 1949-; Young, Marilyn Blatt (New York : New Press : Distributed by W.W. Norton, 2009)
From the Publisher: A groundbreaking historical analysis of indiscriminate bombing from the advent of aircraft to the present war in Iraq.
Introduction / Yuki Tanaka -- 1: British "humane bombing" in Iraq during the interwar era / Yuki Tanaka -- 2: Bombing campaigns in World War II: the European theater / Ronald Schaffer -- 3: Bombing war in Germany, 2005-1940: back to the future? / Robert G Moeller -- 4: Forgotten holocaust: U S bombing strategy, the destruction of Japanese cities, and the American way of war from the Pacific war to Iraq / Mark Selden -- 5: Were the atomic bombings of Hiroshima and Nagasaki justified? / Tsuyoshi Hasegawa -- 6: Strategic bombing of Chongqing by Imperial Japanese army and naval forces / Tetsuo Maeda -- 7: Bombing civilians from the twentieth to the twenty-first centuries / Marilyn B Young -- 8: United States and strategic bombing: from prophecy to memory / Michael Sherry -- 9: Bombing and the morality of war / C A J Coady -- 10: Aerial bombardment of civilians: the current international legal framework / Timothy L H McCormack and Helen Durham -- Notes -- About the contributors -- Index.
Includes bibliographical references (p. [239]-271) and index.
Keywords: History 1900-2000; Military history, Modern -- 20th century; Civilian war casualties -- History -- 20th century; Bombing, Aerial -- History -- 20th century; World War, 1939-1945 -- Casualties; World War, 1939-1945 -- Aerial operations, American